Metoda Kombinasi Modulasi Pergeseran Tingkat Lebar Pulsa dengan Variabel Frekuensi Pembawa Pada Inverter Model Jembatan: Combination Method Of Level Shift Pulse Width Modulation With Carrier Frequency Variables On A Bridge Model Inverter - Wiryajati, I Ketut; I Nyoman Wahyu Satiawan; Ida Bagus Fery Citarsa; I Made Budi Suksmadana; Supriono (Journal of Computer Science and Informatics Engineering (J-Cosine), 2024)
Switching is very important in energy conversion systems. The conversion process requires a good and reliable method. This research identifies methods or techniques for pulse width modulation. This technique proposes a new model of modulation technique, namely by combining level shifted modulation techniques, and adjusting the frequency in such a way that it produces a signal that suits the inverter's needs. The inverter tested in this research is an inverter with a bridge model configuration. The proposed research and methods were verified using MATLAB and Simulink software. The results obtained are the ratio of total harmonic distortion (THD) are 25.07%, 76, 66% and 9.183%, respectively